X-ray Absorption Near Edge Structure (XANES) Spectrum Interpretation for LiFePO4-Silicon Doped Cathode Material - Sahara Hamas Intifadhah; Kholis Nurhanafi; Fahmi Astuti; Rahmawati Munir; Dadan Hamdani; Darminto Darminto (Universitas Andalas, 2023)
LiFePO4-Silicon doped has been widely developed as a battery cathode material. Due to the doping of silicon atoms, this study aims to determine the peak energy (E0), oxidation state and percentage of component composition for Fe K-edge. The experimental sample used are LFP Si-0%, LFP Si-1%, LFP Si-3% and LFP Si-6%. These samples were characterized using XAS (X-ray Absorption Spectroscopy). XANES spectrum showed the peak energy of Pre-edge area is 7113.08 – 7114.49 eV. The oxidation state of Fe atoms were increased and tend to be Fe3+ than Fe2+. Moreover, Linear Combination Fitting (LCF) used to determine the ratio composition FeO/Fe2O3 in experimental samples. The ratio composition indicated Fe atom is multivalent, when the percentage of silicon-doped increases, the ratio of Fe3+ increased.It has been found that the presence of silicon atoms in the LiFePO4 structure has an effect in electronic structure.